PENYULUHAN BUDIDAYA IKAN NILA DI KERAMBA APUNG DESA MARGALUYU KECAMATAN PENGALENGAN KABUPATEN BANDUNG - Budilaksono, Sularso; Novianti, Eva; Karjono, Albertus; Dyh Prinajati, Purnomosutji; Dewi, Euis Puspita; Sovitriana, Rilla; Nasution, Evi Syafrida; Effendi, Maya Syafriana; Farida, Farida; Sujatini, Siti; Pramestari, Diah; Sakti, Essy Malays Sari (Jurnal Abdi Insani, 2024)
Counseling on tilapia cultivation in floating cages was carried out in Margaluyu Village, Pengalengan District, Bandung Regency and was carried out on March 1-2 2024. Margaluyu Village has potential for fisheries because it has 2 large lakes in the village. This activity is to increase people's knowledge and skills in this field. This community service aims to exchange ideas with value fish farmers in floating cages and provide information on this and its impact on the development of tilapia cultivation and the welfare of local communities. The extension methods used include lectures, field observations, group discussions and practical extension. The results of this community service show the community's active participation in extension activities, with a significant level of knowledge and skills after participating in the program. The evaluation also showed positive changes in the community's understanding and knowledge regarding tilapia cultivation. Thus, it can be concluded that outreach activities on tilapia cultivation in floating cages have a positive impact on developing local fisheries potential and community welfare in Margaluyu Village, Pengalengan District, Bandung Regency.